Malaysian Females With Congenital Adrenal Hyperplasia: Surgical Outcomes and Attitudes - Zainuddin, Ani Amelia; Grover, Sonia Regina; Soon, Chong Hong; Nur Azurah, Abdul Ghani; Mahdy, Zaleha Abdullah; Wu, Loo Ling; Rasat, Rahmah; Harun, Fatimah; Chia, Wee Yan; Shamsuddin, Khadijah (Frontiers in Pediatrics, 2019)
Background: Girls born with congenital adrenal hyperplasia have virilised external genitalia. There is considerable debate regarding both the outcomes of feminizing genitoplasty and timing of the surgery in this population. Objective: To investigate outcomes of females 46,XX individuals with CAH in Malaysia, the surgical outcomes of feminizing genitoplasty (FG) and their attitudes towards surgery. Study Design: This is a cross-sectional study involving the two main tertiary centres in Malaysia. All 46,XX patients with CAH and raised female, who had undergone FG were identified and invited to participate. Data on socio-demographic, medical profiles, and attitudes towards surgery were collected. A standardized evaluation of the external genitalia was undertaken including the anatomic and cosmetic evaluation by independent gynaecologists. Results: Of 61 individuals identified, 59 participated - consisting of children (n = 12), adolescents (n = 29) and adults (n = 18). All but one had classical CAH (98.3%) and had undergone FG (n=55, 93.2%) with surgery mostly undertaken by paediatric surgeons trained in DSD work (n=44, 74.6%). Complications overall were low (20.3%), with repeat surgery rate of 9.1%. External genital examination was performed in 38 participants. In all age groups 36.8% had absent clitoral glands and 39.5%% had a persistent urogenital sinus and in 10.5%, no vaginal orifices were seen. Poor cosmetic outcomes were present in 42.1% with 55.3% recommended for further assessment under general anaesthetic. Almost half participants did not venture an opinion on FG, those who did varied from having a positive attitude towards it (18 participants) to 3 opining that it should not be done, or avoided or delayed. From the participants, 35.5% preferred FG to be done early in life compared to 44.0% of the parents. Conclusions: The reoperation rates of the feminizing genitoplasty surgeries were low however due to the anatomic and cosmetic outcomes, reassessment of the external genitalia of these CAH patients may be required once they consider becoming sexually active as they may require further treatment. Many factors such as cultural sensitivities and access to medical treatment and late diagnoses have an impact on attitudes towards FG.